Stigmatisasi Radikal Terhadap Pendidikan Islam: Critical Pedagogy pada Pendidikan dan Pengajaran Pesantren - Malik, Abdul (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This article is intended to explain the issue of radical stigmatization of the pattern of Islamic education, especially Islamic boarding schools. The pattern of pesantren education tends to be suspected of being radical since several ustadz and the administrators of the pesantren have become suspects in the national terrorist case. The widespread issue of links between terrorism and Islamic boarding schools encourages a review of how education and teaching are carried out in Islamic boarding schools. So far, pesantren have been suspected of being educational institutions that support radical values. This study uses a phenomenological qualitative approach with a focus on critical pedagogy as to why there is a radical stigmatization of Islamic boarding schools. The results of the study reveal several aspects of Islamic boarding schools which are indicators of radical stigmatization in these Islamic boarding schools, including curriculum, exclusive religious understanding and attitudes, and learning processes that tend to be indoctrinated.